“I’m missing something”: (non) nativeness in prospective teachers as spanish and English speakers - Viáfara, John Jairo (Colombian Applied Linguistics Journal, 2016)
Rooted in the need to confront the pervasive and harmful effect of the myth of the native speaker and affiliated language ideologies, this article shares the findings of a research study conducted in two public Colombian universities. The study examined participants’ self-perceived (non) nativeness as speakers of Spanish and English. Using surveys and interviews within a qualitative approach, the study found that participants perceived themselves as over-empowered in their being native Spanish speakers. Conversely, as speakers of English, most prospective teachers feared the disadvantages of not achieving native-like abilities, but they were confident in their university programs and their previous experience as English users’ to achieve their language learning education goals.